Effects of sunscreen exposure on Posidonia oceanica (L.) Delile under a perspective of increased seawater temperature scenario - García-Márquez, Manuela Gertrudis; Muñoz Entrena, Sandra; Clément, Cassandra; Agawin, Nona S. R. (Frontiers in Marine Science, 2024)
The environmental risk of coastal sunscreen pollution and ocean warming to seagrass meadows seems to be greatly intensified in the Mediterranean basin, due to its semi-enclosed nature that limits water renewal and the high influx of tourists it receives every year. Both stress factors could be interacting synergistically, thus, contributing to the current decline of Posidonia oceanica meadows. Our study aimed to determine the response of P. oceanica to the combined effects of elevated seawater temperature and sunscreen addition in a short-term laboratory experiment, testing an environmentally relevant sunscreen concentration in Mallorca, Spain (20 mg L-1) and a control (0 mg L-1) with the ambient temperature in spring (15°C) and a worst-case scenario of estimated temperature increase by 2100 (ambient + 5°C). Sunscreen addition promoted net primary production rates in the seagrass under ambient temperature, possibly due to nutrient enrichment from the mixture. Alkaline phosphatase activity (APA) in young leaves was enhanced under increased temperature only. Early-warning signs of the impacts of combined elevated temperature with sunscreen exposure in P. oceanica were the drastic decrease in leaf chlorophyll concentrations and inhibition of the nitrogen fixation associated with rhizomes (more than 50%), along with greater oxidative stress biomarkers in leaves (i.e., catalase activity and polyphenols content) and APA in roots (4-fold increase). The current investigation has revealed how the negative effects of coastal sunscreen pollution in this seagrass species may be exacerbated under climate change factors, such as ocean warming, with possible implications in the nutrient cycling and photosynthetic process of the plant. Investigations focused on determining the impacts of these contaminants in P. oceanica meadows and their interaction with additional stress factors in the environment is of great relevance for the future management of this declining ecosystem.